FRAMING NEWS ON RELIGION AND LIVING ENVIRONMENT IN ONLINE MEDIA - Vanesa Bella Sadmego; Muchammad Nasucha (Program Studi Ilmu Komunikasi, 2019)
In some decades, we have encountered complex and multi-global situation. The crisis has appeared more multifarious, time by time. Some authors and media indicate religion as the crucial factor should be involved to overcome this problem. Media frequently uncover the role of religion in relating environmental crisis. Based on the background, this research aims to find out how the online news media frame religion and the living environment topic. Here, the researchers used framing theoretical conceptual and methods that are adopted from some authors. In this research the news selected by related keywords through search engine. The result shows even though the concern is similar the story or narration are various in presenting the issue of the important stance of religion in dealing with environment. Some nonverbal features used to describe how the story involving the crucial actors and the related event(s).Keyword : religion, living environment, framing analysis, media online